2017
DOI: 10.1002/cbdv.201700165
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Phytoconstituents from Mussaenda roxburghii and Studies of Their Antibiofilm Effect

Abstract: In the context of ethno botanical importance with no phytochemical investigations, Mussaenda roxburghii have been investigated to explore it's phytoconstituents and studies of their antibiofilm activity. Four compounds have been isolated from the aerial parts of this plant and were characterized as 2α,3β,19α,23-tetrahydroxyurs-12-en-28-oic acid (1), β-sitosterol glucoside (4), lupeol palmitate (5), and myoinositol (6). All these compounds were tested for antibacterial and antibiofilm activity against Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The results revealed that the new compound was β-sitosterol-D-glucoside (β-SDG). 25 β-SDG Inhibition of BC-Cell Proliferation in Vitro. To assess what happens upon β-SDG treatment, the MCF7 and MDA-MB-231 BC cell lines as well as the control normal MCF-10A breast cell line were treated for 24 h with various doses of β-SDG, and MTT and colony-formation assays were used to quantify cell viability and proliferation, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results revealed that the new compound was β-sitosterol-D-glucoside (β-SDG). 25 β-SDG Inhibition of BC-Cell Proliferation in Vitro. To assess what happens upon β-SDG treatment, the MCF7 and MDA-MB-231 BC cell lines as well as the control normal MCF-10A breast cell line were treated for 24 h with various doses of β-SDG, and MTT and colony-formation assays were used to quantify cell viability and proliferation, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Cytoplasmic cytochrome c release is a key step of the mitochondria-mediated apoptotic pathway regulated by the Bcl-2 protein family. 25 We thus assessed expression of cytochrome c and the Bcl-2 family, which consists of members that either promote or inhibit apoptosis. 26 As shown in Figure 6C, β-SDG significantly elevated proapoptotic Bax and Bad levels, and simultaneously reduced the antiapoptotic Bcl-2 and Bcl-xl levels, and cytochrome c expression was also upregulated by β-SDG (Figure S5).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter diffuses toward the surrounding cells initiating QS, interacts lasR with the transcription factor, and activates multiple virulence genes, including lasB. In silico docking studies with proteins, like the las family (lasA, lasI, and lasR), luxR, and pil family (pilB, pilT, and pilY1), showed that tormentic and 23-hydroxycorosolic acids [40], as well as a third ursane triperpene, 23-hydroxytormentic acid from Mussaenda roxburghii [41], have good binding affinity with all the selected proteins.…”
Section: Terpenoidsmentioning
confidence: 99%
“…The study on albino mice reported MR at the dose of 600 mg/kg produce toxicity concerning food intake, body weight (BWT), and general appearances [6]. The phytochemical analysis has reported that Mussaenda genus presents active phytochemical iridoids, triterpenes, and flavonoid and also, other phytochemicals such as beta-sitosterol glucosides, lupeol palmitate, and myoinositol [7,8]. Dietary sterol glucosides were neurotoxic to motor neurons [9].…”
Section: Introductionmentioning
confidence: 99%